Multimodal features of assessment in Indonesian conversation: A conversation analysis study - Oktarini, Kadek Ratih Dwi (Universitas Pendidikan Indonesia, 2020)
Assessment is one type of action in interaction. It is very common, as it can appear in any conversation and context. The term assessment broadly covers any evaluative action in interaction. The simplest form of assessment contains an assessable (entity or reference being evaluated) and an assessment (the evaluation towards the assessable). The current study is a preliminary study which explores the multimodal structure of assessment in Indonesian conversation. The method employed is Conversation Analysis. The data is taken from 6 hours of video recorded naturally occurring Indonesian conversation, involving a different number of participants. The current analysis suggests that assessment is a two-steps action which involves firstly the orientation to a focal point, and subsequently the production or display of evaluation towards that focal point. Evaluation can be produced verbally, displayed through non-verbal means, or a combination of the two. The non-verbal evaluation may be produced early in the turn, almost concurrent with the production of the assessable, which is earlier than its verbal counterpart. The current study adds to our understanding of the multimodal structure of conversational interaction, especially on conversational Indonesian, a language variety widely used in Indonesian society, yet receives very limited research attention.